Syntactic Means of Expressiveness in Social Network Discourse - Krutko, Tetiana (Studia Philologica, 2024)
The paper explores how syntactic means can be deployed in social network posts. The purpose of the article is to identify the key syntactic means employed in Ryan Reynolds’ Facebook posts. For the purposes of this study, 700 Ryan Reynolds’ Facebook textual posts have been extracted and analyzed. The data were sourced from Ryan Reynolds’ personal Facebook page between 2016-2024. The methodology employed in this paper has gone through a process of data collection, data processing, and data analysis. Qualitative and quantitative content analyses have been carried out. The textual posts have been explored through functional analysis to investigate syntactic means of expressiveness from the viewpoint of their role in message content. The author of the paper has found out quantitative differences in the usage of the syntactic expressive means by the celebrity. According to investigation, every third textual post comprises expressive syntactic means. Ellipsis, nominative sentences, and parceling have been identified in the given research as the most frequently employed syntactic means in Ryan Reynolds’ Facebook text posts. The result of the research explicates that nominative and elliptical sentences are marked by the highest frequency of use and are employed to add to expressiveness of celebrity’s textual messages. The analyzed linguistic material demonstrated that the main function of elliptical, nominative sentences and parceling is to compress the utterance, make it definite, enhance its expressiveness, create casual, informal and easy-going tone. Syntactic means have been proved to be an effective means of fulfilling the expressive function as they tend to attract recipients’ attention and fascinate them, provoke positive feelings, create the desired impression and a favorable attitude towards the content posted on Facebook.